Overexpression of a SDD1-Like Gene From Wild Tomato Decreases Stomatal Density and Enhances Dehydration Avoidance in Arabidopsis and Cultivated Tomato - Morales-Navarro, Samuel; Pérez-Díaz, Ricardo; Ortega, Alfonso; de Marcos, Alberto; Mena, Montaña; Fenoll, Carmen; González-Villanueva, Enrique; Ruiz-Lara, Simón (Frontiers in Plant Science, 2018)
Stomata are microscopic valves formed by two guard cells flanking a pore, which are located on the epidermis of most aerial plant organs and are used for water and gas exchange between the plant and the atmosphere. The number, size and distribution of stomata are set during development in response to changing environmental conditions, allowing plants to minimize the impact of a stressful environment. In Arabidopsis, STOMATAL DENSITY AND DISTRIBUTION 1 (AtSDD1) negatively regulates stomatal density and optimizes transpiration and water use efficiency (WUE). Despite this, little is known about the function of AtSDD1 orthologs in crop species and their wild stress-tolerant relatives. In this study, SDD1-like from the stress-tolerant wild tomato Solanum chilense (SchSDD1-like) was identified through its close sequence relationship with SDD1-like from Solanum lycopersicum and AtSDD1. Both Solanum SDD1-like transcripts accumulated in high levels in young leaves, suggesting that they play a role in early leaf development. Arabidopsis sdd1-3 plants transformed with SchSDD1-like under a constitutive promoter showed a significant reduction in stomatal leaf density compared with untransformed sdd1-3 plants. Additionally, a leaf dehydration shock test demonstrated that the reduction in stomatal abundance of transgenic plants was sufficient to slow down dehydration. Overexpression of SchSDD1-like in cultivated tomato plants decreased the stomatal index and density of the cotyledons and leaves, and resulted in higher dehydration avoidance. Taken together, these results indicate that SchSDD1-like functions in a similar manner to AtSDD1 and suggest that Arabidopsis and tomatoes share this component of the stomatal development pathway that impinges on water status.